The black sociologists: The first half century. Ed. by J.H. Bracey, Jr., A. Meier [and] E. Rudwick (Belmont, California, Wadworth, 1971)
A Wadsworth series: Explorations in the black experience. General editors: J.H. Bracey, Jr. a.o.